1998
DOI: 10.1128/mcb.18.11.6777
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CREB Binding Protein in Expression of Major Histocompatibility Complex Class II Genes via Interaction with the Class II Transactivator

Abstract: The class II transactivator (CIITA) is a key regulatory factor that controls expression of the major histocompatibility complex (MHC) class II genes that are essential components for antigen presentation and thus regulation of the immune response. We show here that the adenovirus E1A protein interferes with the action of CIITA and inhibits both B-cell-specific and gamma interferon (IFN-γ)-induced expression of MHC class II promoters. Transfection studies provide evidence for the functional role of the CREB-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
138
0
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 45 publications
4
138
0
5
Order By: Relevance
“…These observations, together with the finding that CIITA does not alter the stability of the higher order multiprotein complexes that bind to the class II promoter (37), supports the thesis that the CIITA complex enhances access of transcription factors to DNA binding sites by altering chromatin. Several recent studies have reported (2,38,39) that the histone acetyltransferase cofactor CBP/p300 binds to CIITA and significantly enhances its activity. TSA, at least in part, could replace the function of a CIITA-CBP/p300 coactivator complex by acetylating histones and relieving nucleosome repression allowing promoter occupancy and some level of transcription in the absence of CIITA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations, together with the finding that CIITA does not alter the stability of the higher order multiprotein complexes that bind to the class II promoter (37), supports the thesis that the CIITA complex enhances access of transcription factors to DNA binding sites by altering chromatin. Several recent studies have reported (2,38,39) that the histone acetyltransferase cofactor CBP/p300 binds to CIITA and significantly enhances its activity. TSA, at least in part, could replace the function of a CIITA-CBP/p300 coactivator complex by acetylating histones and relieving nucleosome repression allowing promoter occupancy and some level of transcription in the absence of CIITA.…”
Section: Discussionmentioning
confidence: 99%
“…MHC class II expression is tightly regulated primarily at the level of transcription by multiple transcriptional activators binding to the W/S, X, and Y box promoter sequences. In addition, coactivators, such as class II transactivator (CIITA), 3 Bob1, and CBP/p300, play important roles in the transcriptional regulation of class II (1)(2)(3). Recently, CIITA has been reported to facilitate IFN-␥ induction of MHC class I in addition to class II Ags (4,5), and this, together with the similarities in the structure of the class I and II promoters (6), suggests a commonality in the regulation of MHC genes.…”
mentioning
confidence: 99%
“…The histone H4 code for acetylation of HLA-DRA was previously found to be limited to acetylation of K8 in B cells. H4 K8 acetylation can be catalyzed by CREBbinding protein (CBP)/p300 and P300/CBP-associated factor (35), coactivators shown to interact with CIITA and are necessary for its maximal activity (16,17,36). In IFN-␥-stimulated fibroblasts, additional time-dependent increases observed for histone H4 acetylation at DRA-X included K12 and possibly K5.…”
Section: Figurementioning
confidence: 99%
“…The N-terminus of CIITA contains a transcriptional activation domain, which binds and recruits to MHC class II gene promoters factors involved in chromatin remodeling and modification, as well as components of the general transcriptional machinery (Fontes et al, 1997(Fontes et al, , 1999Kanazawa et al, 2000;Kanazawa and Peterlin, 2001;Kretsovali et al, 1998;Mahanta et al, 1997;Mudhasani and Fontes, 2002;Spilianakis et al, 2000;Zika et al, 2003). These and other observations have strongly implicated CIITA in regulating chromatin structure as a mechanism of activating gene transcription (Zika and Ting, 2005).…”
Section: Introductionmentioning
confidence: 96%